Elbasvir/Grazoprevir for Patients With Hepatitis C Virus Infection and Inherited Blood Disorders: A Phase III Study. Issue 3 (20th July 2017) - Hézode, Christophe; Colombo, Massimo; Bourlière, Marc; Spengler, Ulrich; Ben‐Ari, Ziv; Strasser, Simone I.; Lee, William M.; Morgan, Leslie; Qiu, Jingjun; Hwang, Peggy; Robertson, Michael; Nguyen, Bach‐Yen; et al.
Abstract : Direct‐acting antiviral agents have not been studied exclusively in patients with inherited blood disorders and hepatitis C virus (HCV) infection. The objective of the randomized, placebo‐controlled, phase III C‐EDGE IBLD study was to assess the safety and efficacy of elbasvir/grazoprevir (EBR/GZR) in patients with inherited bleeding disorders and HCV infection. One hundred fifty‐nine adults with HCV infection and sickle cell anemia, thalassemia, or hemophilia A/B or von Willebrand disease were enrolled at 31 study sites in the United States, Europe, Australia, Canada, Israel, and Thailand. Patients were given an oral, once‐daily, fixed‐dose combination of EBR/GZR 50 mg/100 mg for 12 weeks and randomized to the immediate‐treatment group (ITG) or deferred‐treatment group (DTG; placebo followed by active treatment). The primary endpoints were the proportion of patients in the ITG with unquantifiable HCV RNA 12 weeks posttreatment (sustained virological response 12 weeks after completion of study treatment; SVR12) and the comparison of safety in the ITG and DTG. In the ITG, 100 of 107 patients (93.5%) achieved SVR12, 6 relapsed, and 1 was lost to follow‐up. SVR12 was achieved in 94.7% (18 of 19), 97.6% (40 of 41), and 89.4% (42 of 47) of patients with sickle cell disease, β‐thalassemia, and hemophilia A/B or von Willebrand disease, respectively. Serious adverse events were reported by 2.8% (n = 3) and 11.5% (n = 6) of patients in the ITG and DTG, respectively. Hemoglobin levels and international normalized ratio values were similar in patients receiving EBR/GZR and placebo; among patients with hemoglobinopathies, change in mean hemoglobin levels was similar in those receiving EBR/GZR compared to those receiving placebo. Conclusion : These results add to the expanding pool of data available for EBR/GZR, indicating a high level of efficacy and favorable tolerability in patients with HCV infection. (Hepatology 2017;66:736–745)